Systems Analysis of the 22q11.2 Microdeletion Syndrome Converges on a Mitochondrial Interactome Necessary for Synapse Function and Behavior - Avanti Gokhale; Cortnie Hartwig; A. Freeman; Julia L. Bassell; Stephanie A. Zlatic; Christie Sapp Savas; Trishna Vadlamudi; Farida Abudulai; Tyler T. Pham; Amanda Crocker; Erica Werner; Zhexing Wen; et al. (2019)
Neurodevelopmental disorders offer insight into synaptic mechanisms. To unbiasedly uncover these mechanisms, we studied the 22q11.2 syndrome, a recurrent copy number variant, which is the highest schizophrenia genetic risk factor. We quantified the proteomes of 22q11.2 mutant human fibroblasts from both sexes and mouse brains carrying a 22q11.2-like defect,